2445. Efficacy and Tolerability of Linezolid for Treatment of Infectious Spondylitis. (26th November 2018) - Jung, Jongtak; Lee, Eunyoung; Song, Kyoung-Ho; Choe, Pyeong Gyun; Kim, Nam Joong; Kim, Eu Suk; Bang, Ji Hwan; Park, Sang Won; Kim, Hong Bin; Park, Wan Beom; Oh, Myoung-Don
Abstract: Background: Infectious spondylitis requires long-term antibiotic treatment for 6 weeks or more, and the use of intravenous antibiotics during this period causes social loss and costs due to hospitalization. Linezolid has high oral bioavailability and is not affected by changes in renal or hepatic function. We investigated the clinical and microbiological effects of linezolid in infectious spondylitis caused by β-lactam resistant Gram-positive bacteria. Methods: Clinical data about patients who were diagnosed infectious spondylitis and treated with linezolid for more than 4 weeks were collected by electronic medical record retrospectively at 3 tertiary hospitals from 2006 to 2016. Clinical and microbiological success after treatment were determined using medical record or bacterial culture results identified in blood or tissue. Results: Twenty Korean cases were treated with linezolid more than 4 weeks during the study period. Median duration of linezolid treatment was 40.5 days. Major causative organism was methicillin-resistant Staphylococcus aureus ( n = 15), followed by methicillin-resistant coagulase-negative Staphylococcus ( n = 3). In 10 of 20 patients treated with linezolid, antibiotics were changed for side effects or de-escalation of antibiotics. The most common reason for discontinuation of linezolid was thrombocytopenia ( n = 6). Fourteen patients were cured, 4 failed and 2 cases of mortality occurred due to other causes than infectious spondylitis. Nine of 13 patients who were assessed as vancomycin treatment failure were cured. Cytopenia was most common drug adverse reaction, and severe cytopenia (grade II or more of NCI criteria) was 11.11% in neutropenia, 12.96% in anemia and 20.37% in thrombocytopenia. Conclusion: Linezolid can be used as an effective antibiotic agent in patients with infectious spondylitis, especially when treatment failure of the first-line treatment is expected. Linezolid can be administered orally in outpatient clinic, reducing healthcare cost. Since cytopenia (especially thrombocytopenia) are common, a regular follow-up of complete blood cell count is needed. Disclosures: All authors: No reported disclosures.